2023
DOI: 10.1017/dsj.2023.27
|View full text |Cite
|
Sign up to set email alerts
|

Is virtual reality so user-friendly for non-designers in early design activities? Comparing skills needed to traditional sketching versus virtual reality sketching

Noémie Chaniaud,
Sylvain Fleury,
Benjamin Poussard
et al.

Abstract: Virtual reality (VR) sketching has many advantages for product design and tends to be more and more used among designers and non-designers (end-users). Nevertheless, few studies have focused on the skills needed to use VR sketching for non-designers especially VR novices in VR software. This study focuses on identifying the cognitive impact of VR sketching compared to traditional sketching on VR expert and VR novice in an experimental setting. Thirty-one participants composed of VR experts (N = 15) and VR novi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
0
1
Order By: Relevance
“…A recent study by Chaniaud et al (2023) noted that VR sketching can be difficult for people without prior drawing skills or poor visuospatial abilities, but our study suggested that previous drawing skills might not be transferrable. Visualization skills were observed to be less useful in VR compared to tablet and paper drawing in this study, despite the fact that participants noted the intuitive nature of visualizing ideas in this medium.…”
Section: Skill Developmentcontrasting
confidence: 87%
“…A recent study by Chaniaud et al (2023) noted that VR sketching can be difficult for people without prior drawing skills or poor visuospatial abilities, but our study suggested that previous drawing skills might not be transferrable. Visualization skills were observed to be less useful in VR compared to tablet and paper drawing in this study, despite the fact that participants noted the intuitive nature of visualizing ideas in this medium.…”
Section: Skill Developmentcontrasting
confidence: 87%